All Patient Refined-Diagnosis Related Groups’ (APR-DRGs) severity of illness and risk of mortality as predictors of in-hospital mortality - Santos, João Vasco (2022)
Publisher Copyright: © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.